(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
There have been significant changes in strengthening the relationship with the parents, helping to involve parents and supporting parental competencies. In spite of this, pedagogues often notice lack of interest from parents however the help received from pedagogues is not considered sufficient by the parents. To achieve some improvements regarding this situation, it would be necessary to know more about the pedagogues’ opinion on the parents’ educational habits as these concepts have deep impacts on the cooperation between pedagogues and parents. During our pilot investigation we have spoken with kindergarten and early childhood educators about their opinion on the relationship of children to tales/ picture books/ media, how they see their own role in this, their possibilities and their cooperation with parents. During the interviews we got a clear picture on some elements of the parents’ image of the pedagogues. We would like to present some parts of it in our paper.